Giải bài toán điều khiển thiết bị bay không người lái trong mặt phẳng thẳng đứng - Từ, Phan Văn (Journal of Computer Science and Cybernetics, 2016)
The control problem of nonpilot fly equipment is very complex, nonlinear and time-variable. Before it was solved approximately by digital methods. Now there are simulation tools that allow us to solve this problem by new method. These results of solution will give us to see motion characteristics of fly equipment and appropriate conclusion.